Survey Response and Observed Behavior: Emancipative and Secular Values Predict Prosocial Behaviors - Kistler, Deborah (Journal of cross-cultural psychology, 2017)
Since decades, cross-cultural psychology examines moral values using data from standardized surveys, assuming that values guide human behavior. We add to this literature by studying the link between moral values and various forms of prosocial behavior, using data from respondents of the sixth World Values Survey in Germany who participated in an online behavioral experiment. The experiment consists of a series of incentivized tasks and allows us to elaborate the association between survey-measured values and three facets of observed prosocial behavior. The evidence boils down to three findings. While (a) emancipative values relate to higher common pool contributions and (b) higher donations to charitable organizations, (c) secular values are linked with more productive and less protective investments. As these results conform to key theories and reach empirical significance in a major postindustrial nation, we conclude that we have important evidence at hand highlighting the potential of combined survey-experiment methods to establish value–behavior links that are otherwise inexplorable.